The complete mitochondrial genome of a marine gastropod: Umbonium thomasi (Trochida, Trochidae). Issue 1 (2nd January 2019) - Kim, Hana; Yu, Cheol; Kim, Hyung June; Jung, Yun-Hwan
Abstract: The mitogenome sequence of a marine gastropod, Umbonium thomasi (Crosse, 1863) (Trochida, Trochidae), was determined first in the genus Umbonium . The assembled mitogenome, consisting of 15, 998 bp in length, has 13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes. The order and structure of the genes are similar to those of other Trochid species. The overall base composition of mitogenome is 34.8% A, 22.1% C, 14.0% G, and 29.1% T with an A + T bias of 64%. The complete mitogenome of U. thomasi provides essential and important DNA molecular data for further phylogenetic and evolutionary analysis of marine gastropods.